Fertilizer application and water management combined method for improving rice field soil quality and reducing cadmium pollution - SHE ZIJIAN; CHEN YONG; LI YICHUN; WANG BAIBING; LI QI; LUO WEILIN; LI LINFENG; DAI YUAN; LIN XIAOYANG; XU ZISHENG (2023)
The invention relates to the technical field of agricultural pollution control, and provides a fertilizer application and water management combined method for improving rice field soil quality and reducing cadmium pollution, and the method comprises the following steps: (1) applying a base fertilizer in a rice field 3-7 days before rice seedling slinging, and putting water to steep the field; (2) applying a compound fertilizer to the rice field 1-2 days before rice seedling throwing, and putting water to steep the field; (3) after rice seedling slinging, waterflooding irrigation is conducted, shallow water irrigation is conducted 25-30 days after seedling slinging, and drainage and field drying are conducted 3-7 days before rice harvesting. According to the method, it is powerfully guaranteed that the content of Cd in brown rice reaches the national standard (lower than 0.2 mg/kg), the soil environment, fertility and health quality are effectively improved, and the safety and sustainability of utilization of